2016
DOI: 10.1002/app.44676
|View full text |Cite
|
Sign up to set email alerts
|

Green composites of poly(3‐hydroxybutyrate) and curaua fibers: Morphology and physical, thermal, and mechanical properties

Abstract: In this article, we report the morphology and thermal, mechanical and physical properties of poly(3‐hydroxybutyrate) (PHB)/curaua composites containing triethyl citrate (TEC) as the plasticizer. The composites were prepared by mechanical mixing using pristine and chemically treated fibers (10 wt %) and TEC (30 wt %) and characterized by differential scanning calorimetry, dynamic mechanical analysis, X‐ray diffraction, small angle X‐ray scattering, polarized optical microscopy, scanning electron microscopy, ten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
0
13

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(50 citation statements)
references
References 61 publications
4
33
0
13
Order By: Relevance
“…These results indicated that the CpFe + did not have a significant effect on the crystal structure of the PHB, which was in a good agreement with the XRD results, as shown in Figure 4 . A similar trend was reported for the PHB with other nucleating agents [ 20 , 26 , 32 , 57 ]. It is worth mentioning that the width of the half height of the melting peak became narrower in comparison to the PHB.…”
Section: Resultssupporting
confidence: 84%
“…These results indicated that the CpFe + did not have a significant effect on the crystal structure of the PHB, which was in a good agreement with the XRD results, as shown in Figure 4 . A similar trend was reported for the PHB with other nucleating agents [ 20 , 26 , 32 , 57 ]. It is worth mentioning that the width of the half height of the melting peak became narrower in comparison to the PHB.…”
Section: Resultssupporting
confidence: 84%
“…The enlargement of the β relaxation with increasing TEC content is observed clearly. 30 Scalioni et al 26 reported that the addition of TEC at a mass fraction of 0.3 resulted in a decrease in the PHB elastic modulus from 230 to 120 MPa (a decrease of around of 50%) and an increase in the Izod impact resistance of notched and by us were close, however, they used a PHB with M n = 140,000 g/mol while in the present work a PHB with M n = 115,000 g/mol was used. Moreover, they performed tensile tests 30 days after injection molding, while we performed the tensile tests 60 days after processing.…”
Section: Dynamic Mechanical Analysismentioning
confidence: 99%
“…Moreover, its properties may be adjusted by blending with other polymers [17][18][19][20][21] and the use of polymer additives as nucleating additives 22 and plasticizers. [23][24][25][26][27][28][29][30] The main drawbacks that hinder the wide application of PHB are its high stiffness and brittleness imparted by physical aging [31][32][33][34] and the narrow processability window due to degradation temperature close the melting. 35 Several strategies have been used to overcome these barriers, such as the addition of nucleating agents, which increase crystallization rate and reduce spherulite size 22 ; the copolymerization of 3-hydroxybutyrate with other comonomers such as hydroxyvalerate and hydroxyhexanoate, 36 which generates copolymers with increased toughness; and the usage of external plasticizers.…”
Section: Introductionmentioning
confidence: 99%
“…[47,48] The thermal expansion coefficient of PHB (40 µm mK −1 ) is relatively low compared to polyester (125 µm mK −1 ), polyethylene (PE) (200 µm mK −1 ), and PET (59.4 µm mK −1 ). [49] PHB has a high melting temperature (175°C), which should enable stability over a wide range of temperatures. [50] PHB is also highly hydrophobic, which should make PHB-based devices and composites resistant to water.…”
Section: Introductionmentioning
confidence: 99%